Analysis of Symbols in Campaign Women Illustration of “The Beauty from Sabang to Merauke - Ariani Kusumo Wardhani; Hanisa Hasan; Renita Azzhara (Eduvest - Journal of Universal Studies, 2022)
The beauty of women who are very diverse is not limited to physical beauty, but there are many points of view that can be seen; therefore, women are the main target audience in the campaign. The trend of women's beauty is generally much influenced by the socio-cultural background of a society. As in the work of designer Nadya Noor who collaborated with Base, a beauty product company, by creating an illustration applied for campaign on clothing about beauty standardization, this work was inspired by the unique shapes of the big islands in Indonesia, as well as the diversity of women in Indonesia who very diverse. The research method using qualitative methods is to analyze the illustrations on clothes with the delivery of messages in the design. Through this work, the researcher examines the visual elements of fashion illustrations in campaigns with the messages conveyed through visuals in campaigns related to illustrations, colors, layouts, with data collection techniques through library research, documentation and interviews. The illustration can be symbols for Indonesian representation from all rases in Indonesia. The current study also would collaborate with international partner from School of Creative of Technology and Heritage Universiti Malaysia Kelantan. The expertise of the international partner regarding design creative visual issues would be beneficial to conduct the current study. More importantly, such expertise is required within the field of Communication Technology and Creative Industry contribute significantly within the literature, and to strengthen the international exposure of the current study. The research team from UMB would conduct the literature review, data collection, and data analysis. Meanwhile, the international partner from School of Creative of Technology and Heritage UMK would conduct the literature review, mainly on the creative industry construct. Finally, the output of this research is to publish the research result on International Journal of Art and Design Education, which is a indexed international journal.